2010
DOI: 10.1080/10550881003684921
|View full text |Cite
|
Sign up to set email alerts
|

Children of Addicted Women

Abstract: The purpose of this article was to review follow up studies of children with prenatal drug exposure from preschool through adolescence. Specifically, the authors focus on the effects of prenatal exposure to cocaine, methamphetamine, and opiates on behavior and development. The largest number of studies have examined cocaine-exposed children. The authors identified 42 studies that suggest that there are unique effects of prenatal cocaine exposure on 4- to 13-year-old children, particularly in the areas of behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
109
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 184 publications
(210 reference statements)
2
109
0
2
Order By: Relevance
“…Indeed, no longitudinal follow-up studies have extended beyond the first few years of life. 175 Animal experiments have neither proven nor disproven the effects of chronic maternal opioid administration on dendritic growth and development in the fetus. 176,177 Recent observations of delayed or altered maturation of neuronal connective tracts and smaller neuroanatomic volumes in infants born to opioid-addicted mothers 178,179 have established an urgent need for studies of long-term outcomes in these children.…”
Section: Discharge and Follow-upmentioning
confidence: 99%
“…Indeed, no longitudinal follow-up studies have extended beyond the first few years of life. 175 Animal experiments have neither proven nor disproven the effects of chronic maternal opioid administration on dendritic growth and development in the fetus. 176,177 Recent observations of delayed or altered maturation of neuronal connective tracts and smaller neuroanatomic volumes in infants born to opioid-addicted mothers 178,179 have established an urgent need for studies of long-term outcomes in these children.…”
Section: Discharge and Follow-upmentioning
confidence: 99%
“…13 Another review through age 13 years found associations with behavior problems, attention, language, and cognition. 14 Little is known about PCE and adolescent functioning. 14 Adolescence is a transitional period characterized by increased social and cognitive demands, together with increasingly complex executive functioning abilities (eg, abstract reasoning).…”
mentioning
confidence: 99%
“…14 Little is known about PCE and adolescent functioning. 14 Adolescence is a transitional period characterized by increased social and cognitive demands, together with increasingly complex executive functioning abilities (eg, abstract reasoning). 15 It is plausible that the small effects found in attention and emotion regulation among children with PCE early in life may increase during adolescence.…”
mentioning
confidence: 99%
“…They have established that infants born to mothers consuming opioid during gravidity demonstrate less intellectual presentation and disturbed regulation than no exposed infants (48). Opioid children have similarly indicated less neuroanatomical capacities and directories of less significant development of neural tracts than controls (47)(48)(49).…”
Section: Pathophysiology and Etiologymentioning
confidence: 99%
“…Several authors state that 6 year old cocaine exposed boys, not girls, display more hyperactivity and mental complications than no exposed peers (54). Standard gender differences and a fewer ideal mannish prenatal initial point might inter relate by neonatal abstinences and augmented regulation difficulties regularly establish between drug unprotected kids (48).…”
Section: Pathophysiology and Etiologymentioning
confidence: 99%